KOMUNIKASI TERAPEUTIK PERAWAT DENGAN KEPUASAN PASIEN RAWAT JALAN DI RSU GMIM PANCARAN KASIH MANADO - Irma M. Yahya; Rahmat Djalil (Universitas Muhamadiyah Manado, 2021)
Introduction.Effective therapeutic lack of communication between a nurse with patient resulted in the increasingly distress often what happens on patients can refuse to give the act of nursing by therapeutic lack of communication. Purpose of this research is to analyze The Relation of Communication of Nurse’s Therapeutic towards Outpatients’ satisfaction at Rumah Sakit Umum GMIM Pancaran Kasih Manado. This research used descriptive analytic method with cross sectional study approach. The sampling technique in this research used accidental sampling method. Method.Data collecting was conducted by observation and questionnaires. The collected data then processed by SPSS version 16.0. Result.The test result of chi-square got a significant value p=0,000 that shows that p value is smaller than α 0,05. Conclusion.of this research is the researcher found there is a significant relation of Communication of Nurse’s Therapeutic towards Outpatients’ satisfaction at Rumah Sakit Umum GMIM Pancaran Kasih Manado that is showed by the test result of chi-square that got (p) = 0.000 < 0.05. The value of 0,000 is below of value of alpha 5% (0,05).